CreLite: An optogenetically controlled Cre/loxP system using red light. Issue 11 (31st August 2020) - Yen, Shuo‐Ting; Trimmer, Kenneth A.; Aboul‐Fettouh, Nader; Mullen, Rachel D.; Culver, James C.; Dickinson, Mary E.; Behringer, Richard R.; Eisenhoffer, George T.
Abstract: Background: Precise manipulation of gene expression with temporal and spatial control is essential for functional analysis and determining cell lineage relationships in complex biological systems. The cyclic recombinase (Cre)‐ lox P system is commonly used for gene manipulation at desired times and places. However, specificity is dependent on the availability of tissue‐ or cell‐specific regulatory elements used in combination with Cre. Here, we present CreLite, an optogenetically controlled Cre system using red light in developing zebrafish embryos. Results: Cre activity is disabled by splitting Cre and fusing with the Arabidopsis thaliana red light‐inducible binding partners, PhyB and PIF6. Upon red light illumination, the PhyB‐CreC and PIF6‐CreN fusion proteins come together in the presence of the cofactor phycocyanobilin (PCB) to restore Cre activity. Red light exposure of zebrafish embryos harboring a Cre‐dependent multicolor fluorescent protein reporter injected with CreLite mRNAs and PCB resulted in Cre activity as measured by the generation of multispectral cell labeling in several different tissues. Conclusions: Our data show that CreLite can be used for gene manipulations in whole embryos or small groups of cells at different developmental stages, and suggests CreLite may also be useful for temporal and spatial control of gene expression in cell culture, ex vivo organ culture, and other animal models. Key Findings: Created CreLite, an optogenetically-controlled Cre system using red light. Cre activity is disabled by splitting Cre and fusing with red light-inducible binding proteins. Upon red light illumination, the Cre fusion proteins come together to restore Cre activity. Demonstrate CreLite can be used for gene manipulations in whole zebrafish embryos or small groups of cells at different developmental stages. Findings suggest CreLite may also be useful for temporal and spatial control of gene expression in cell culture, ex vivo organ culture, and other animal models